2011
DOI: 10.1097/gco.0b013e3283409c91
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the heparin-binding epidermal growth factor-like growth factor in ovarian cancer therapy

Abstract: We discuss alternative strategies to develop the chemotherapeutic agent based on targeting ErbB family ligands rather than their receptors. A phase I study of CRM197 for advanced ovarian cancer has already begun, which is the first approved trial of ErbB-ligand-targeted therapy. We also discuss clinical adaptations based on combination of CRM197 with other conventional chemotherapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…Although no antibody to an EGF-like molecule has so far been approved for clinical applications, it is notable that an HB-EGF inhibitor (CRM197) is active both as a single agent and in combination with other anticancer agents (Sanui et al , 2010; Tsujioka et al , 2011), and bevacizumab, a therapeutic antibody used to treat colorectal and other tumors, can intercept the vascular endothelial growth factor (VEGF). In contrast to the VEGF family, the greater multiplicity of the EGF family ligands calls for a more general approach, such as the “tailor made” strategy we developed (Lindzen et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although no antibody to an EGF-like molecule has so far been approved for clinical applications, it is notable that an HB-EGF inhibitor (CRM197) is active both as a single agent and in combination with other anticancer agents (Sanui et al , 2010; Tsujioka et al , 2011), and bevacizumab, a therapeutic antibody used to treat colorectal and other tumors, can intercept the vascular endothelial growth factor (VEGF). In contrast to the VEGF family, the greater multiplicity of the EGF family ligands calls for a more general approach, such as the “tailor made” strategy we developed (Lindzen et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous phase II clinical studies with imatinib and gefitinib in patients with refractory or recurrent EOC suggested that although these agents have marginal benefits as monotherapies in EOC, their ability to modulate molecular targets (e.g., EGFR, c-Kit, PDGFR, ERK, AKT) and demonstrate proof of concept corroborates their applicability in combinatorial molecular therapeutics [198, 199]. A number of reports have reinforced the notion that inhibition of a single transduction pathway may be insufficient since activation of alternative signaling cascades may conceal efficacy, and that it would be more advantageous to target integrated cancer signals, for example, VEGFR- and EGFR-interdependent pathways [170] and heparin-binding epidermal growth factor-like growth factor (HB-EGF) [200, 201]. Remarkably also, the mammalian target of rapamycin (mTOR) is a central intracellular kinase that not only orchestrates proliferation, survival, and angiogenic pathways, but has also been linked to resistance to EGFR antagonists, and thus mTOR inhibition could be explored to interfere with tumor growth and expansion at multiple levels [4, 83, 84, 92, 159, 170, 202205].…”
Section: Ovarian Cancer Biomarkers and Cellsignaling Pathwaysmentioning
confidence: 90%
“…IL-6 and IL-8 are also important contributors to ovarian cancer angiogenesis, as demonstrated in preclinical models (34 -36). A few preclinical studies demonstrated the efficacy of different HB-EGF inhibitors in the reduction of ovarian tumor growth when administered alone or in combination with paclitaxel (37,38). Thus modulation of expression of multiple angiogenic cytokines through HB-EGF represents an attractive opportunity to target ovarian tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%